2021
DOI: 10.1016/j.annonc.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Updated estimates of eligibility for and response to genome-targeted oncology drugs among US cancer patients, 2006-2020

Abstract: Prior studies have evaluated the percentage of cancer patients with advanced or metastatic cancer who are eligible for and respond to genome-targeted therapy, but since that publication, the number of Food and Drug Administration (FDA) approvals for drugs targeting genetic indications has grown rapidly. We sought to update the estimates of both eligibility for and response to genome-targeted and genome-informed therapies in US cancer patients for FDA-approved drugs to reflect estimates as of 2020. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 13 publications
0
45
0
Order By: Relevance
“…Molecularly targeted therapeutics have revolutionized cancer therapy. However, because as many as 85% of cancer patients are currently ineligible for targeted therapies (Haslam et al, 2021), there remains an urgent need to match patients with effective drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Molecularly targeted therapeutics have revolutionized cancer therapy. However, because as many as 85% of cancer patients are currently ineligible for targeted therapies (Haslam et al, 2021), there remains an urgent need to match patients with effective drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The responses to targeted therapy has increased from approximately 3% in 2006 to 7% in 2020 [ 4 ], which gives hope to the field of precision medicine. Precision medicine trials reports of only 8–27% actually receiving targeted treatment [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and response rates of 0.8–3% [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in advanced Non-Small Cell Lung Cancer (NSCLC), treatment options have evolved with epidermal growth factor receptor ( EGFR ), anaplastic lymphoma kinase ( ALK )- and ROS proto-oncogene 1 ( ROS1 ) directed treatment [ 1 , 2 , 3 ]. Despite the increasing eligibility and response to genome-targeted therapy from 2006 (3%) to 2020 (7%) [ 4 ], the clinical benefit of precision medicine, beyond standard of care treatments, is still described as uncertain [ 5 ]. Real-time studies in advanced NSCLC have not yet demonstrated any improvements in survival by comprehensive molecular profiling [ 6 , 7 , 8 ], but this scenario might change due to an increasing numbers of promising targeted treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Approvals for genome-informed indications, which are often based on ORR, have been increasing in recent years. Currently, 13.6% of US cancer patients are eligible for genome targeted drugs and 7% of cancer patients may respond [3]. However, it is unknown what percentage of these drugs have proven OS gains for these indications and what the magnitude of those differences are.…”
Section: Introductionmentioning
confidence: 99%